2015
DOI: 10.4103/0189-6725.172565
|View full text |Cite
|
Sign up to set email alerts
|

Parental circumcision preferences and early outcome of plastibell circumcision in a Nigerian tertiary hospital

Abstract: Background:Parents are central in decisions and choices concerning circumcision of their male children and plastibell circumcision is a widely practiced technique. This study determined parental preferences for male neonatal and infant circumcisions and evaluate the early outcomes of plastibell circumcisions in a tertiary centre.Patients and Methods:This is a prospective study on consecutive male neonates and infants who were brought for circumcisions at Nnamdi Azikiwe University Teaching Hospital Nnewi, South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 15 publications
2
25
0
Order By: Relevance
“…In our clime, most circumcision is performed by traditional circumcisionists, traditional birth attendants, nurses, and hospital ward attendants, sometimes with major complications such as urethrocutaneous fistula, excessive post circumcision bleeding, and glans amputation. [5,17,19,26,27] The result of our study showed that the bone cutter method performed better than the plastibell method in terms of the average amount of blood loss and duration of surgery. The Hollander wound evaluation scale and parental satisfaction as measured by the penile perception score were similar in both groups, even though the level of parental satisfaction was higher among those who had bone-cutter technique.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In our clime, most circumcision is performed by traditional circumcisionists, traditional birth attendants, nurses, and hospital ward attendants, sometimes with major complications such as urethrocutaneous fistula, excessive post circumcision bleeding, and glans amputation. [5,17,19,26,27] The result of our study showed that the bone cutter method performed better than the plastibell method in terms of the average amount of blood loss and duration of surgery. The Hollander wound evaluation scale and parental satisfaction as measured by the penile perception score were similar in both groups, even though the level of parental satisfaction was higher among those who had bone-cutter technique.…”
Section: Discussionmentioning
confidence: 90%
“…Many studies suggested that plastibell circumcision is a simple method and minor complications include local sepsis, bleeding, bell impaction, dysuria, incomplete separation of plastibell device, proximal migration of the ring, and excessive or inadequate skin removal. [17,23,29] However, case series of significant complications have also been reported. This includes necrotizing fasciitis, urinary retention, and glans necrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They adduced the study findings to the settings (Abuja and Lagos) in which preponderance of the patients were Yorubas and Ibos, who typically circumcise their children earlier and often within the first few days of life. Ekwunife et al [6] in a study conducted at Nnamdi Azikwe University Teaching Hospital, Nnewi (southeastern Nigeria), reported an age range of 2-140 days, and 73.9% of the parents would prefer circumcision to be carried out on the 8th day of life.…”
Section: Discussionmentioning
confidence: 99%
“…Circumcision is surgical removal of prepuce that covers the glans penis 5 Circumcision is a desirable public health intervention and an old custom being practiced in various communities for a long time. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] It is one of the most common male surgical procedure performed globally with one in three males circumcised worldwide. It is performed in Muslim and Jew communities as a religious tradition with almost two-thirds of circumcised males worldwide being Muslims.…”
Section: Introductionmentioning
confidence: 99%